Implementasi Model TAM pada Sistem Informasi Presensi Online Menggunakan Face Recognition dan GPS - Yusuf Wahyu Setiya Putra (Indonesian Society of Applied Science, 2023)
This study aims to analyze system user acceptance of online attendance information systems with face recognition and GPS using the variables Perceived Ease of Use, Perceived Usefulness and Attitude toward Using contained in the TAM model. (Technology Acceptance Model). Respondents used as many as 45 people consist of teachers, teaching staff and students. Questionnaires were used to obtain data that had been tested for validity and reliability which were then analyzed using multiple linear regression techniques. The results of the analysis of the 1st regression equation show that the variable Perceived Usefullness (X1) has a significant influence on the variable Attitude toward Using (Y) with a t count of 4.114 with a significance of p = 0.000 (<0.05). The variable Perceived Ease of Use (X2) has a significant effect on the variable Attitude Toward Using (Y) with t count 2.898 with a significant p = 0.010 (<0.05). The results of the analysis of the second regression equation show that the variables X1 and X2 together have a significant effect on Attitude toward Using (Y) because the statistical value F count = 23.556 with a significance p = 0.000 (<0.05).